The Role of Development Communication in Enhancing Community Involvement in Bur Telege Tourism Management - Agung Pangeran Bungsu; Nur Sa’adah (Ali Institute of Research and Publication, 2026)
This study examines the critical factors influencing the sustainability of community-based tourism management in Bur Telege, Aceh Tengah, and investigates the effectiveness of development communication in promoting community engagement. The study is based on the assumption that genuine local participation in tourism governance requires open, transparent, and inclusive communication. Using an Explanatory Sequential Mixed Methods (ESMM) design, the research involved 100 respondents through a Likert-scale questionnaire, complemented by in-depth interviews with six key informants. Quantitative findings indicate that development communication has a significant impact on community engagement, with a Pearson correlation value (r = 0.61; p < 0.01) and explaining 37% of the variance in participation levels (R² = 0.37). However, the mean score suggests that communication effectiveness remains relatively low (mean = 2.1), particularly in meeting attendance (1.7) and the timeliness of information delivery (1.9). Qualitative analysis using NVivo identified several supporting factors, including government support through workforce certification programs, the use of simple digital media (such as WhatsApp), religion-based social capital, and village meetings. Conversely, significant barriers include the absence of a comprehensive tourism development blueprint, nepotism in recruitment practices, community pragmatism, lack of transparency in village-owned enterprise (BUMDes) management, and limited representation of marginalized groups. These findings underscore that effective development communication is a crucial instrument for strengthening long-term community engagement. Therefore, digital-based, transparent, and participatory communication strategies are essential to ensure sustainable tourism management.